A mathematical model of white blood cell dynamics during maintenance therapy of childhood acute lymphoblastic leukemia - Le, Thuy T.T.; Jost, Felix; Raupach, Thomas; Zierk, Jakob; Rauh, Manfred; Suttorp, Meinolf; Stanulla, Martin; Metzler, Markus; Sager, Sebastian (Mathematical Medicine and Biology, 2019)
Acute lymphoblastic leukemia is the most common malignancy in childhood and requires prolonged oral maintenance chemotherapy to prevent disease relapse after remission induction with intensive intravenous chemotherapy. In maintenance therapy, drug doses of 6-mercaptopurine (6-MP) and methotrexate (MTX) are adjusted to achieve sustained antileukemic activity without excessive myelosuppression. However, uncertainty exists regarding timing and extent of drug dose responses and optimal dose adaptation strategies. We propose a novel comprehensive mathematical model for 6-MP and MTX pharmacokinetics, pharmacodynamics and myelosuppression in acute lymphoblastic maintenance therapy. We personalize and cross-validate the mathematical model using clinical data and propose a real-time algorithm to predict chemotherapy responses with a clinical decision support system as a potential future application.
CRIS-Team Scopus Importer:2019-12-24
Keywords: chemotherapy; childhood acute lymphoblastic leukemia; maintenance therapy; ordinary differential equations; parameter estimation; real-time algorithm